KNOWLEDGE AND ATTITUDE TOWARDS HEPATITIS B AND HEPATITIS C AMONG DENTAL MEDICINE STUDENTS. - Tatina T. Todorova; Gabriela Tsankova; Dajana Tsankova; Tcvetelina Kostadinova; Neli Lodozova (Peytchinski Publishing, 2015)
Background: Hepatitis B (HBV) and hepatitis C viruses (HCV) are highly contagious and important occupational hazard for health workers. Dental practice often includes direct contact with patients' body fluids and exposure at high degree to potentially HBV and HCV infected materials and instruments. Purpose: The purpose of this study is to investigate the level of knowledge about hepatitis B and C infections and the attitude towards hepatitis B virus vaccination among Dental Medicine students. Materials and Methods: A cross-sectional survey was conducted among 96 students of Faculty of Dental Medicine, Medical University of Varna in March, 2015. The questionnaire contained 22 questions divided into 4 major sections. SPSS ver.16 software package was used for statistical data processing. Results: Most of the participants (82,3 %) considered hepatitis B and C as serious diseases and had positive attitude towards HBV vaccination (75 %). Almost 90 % considered that dental practice could enhance the risk of infection with HBV and HCV. Unfortunately, only 57,4 % of students knew their vaccination status and 13,9 % had checked HBV antibodies' level. Conclusions: The majority of respondents demonstrated a high level of knowledge of HBV and HCV infections. All participants were aware about the risk of potential HBV and HCV transmission in their future practice and anticipated applying preventive measures at work. However, deeper information about HBV vaccination and checking anti HBs titer is still needed among dental students, as well continuous target education in the field.